OUTCOMES OF CEMENTLESS LONG-STEM HEMIARTHROPLASTY FOR INTERTROCHANTERIC FEMORAL FRACTURES IN ELDERLY PATIENTS AT HA DONG GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and subclinical characteristics of elderly patients with intertrochanteric femoral fractures (IFFs) and evaluate the outcomes of cementless long-stem hemiarthroplasty in this patient group at Ha Dong General Hospital.Subjects and Methods: A descriptive study combining retrospective and prospective elements was conducted on 35 patients over 60 years old with traumatic IFFs who underwent cementless long-stem hemiarthroplasty at Ha Dong General Hospital. The study period was reported from June 2022 to June 2024.Results: The average age of the 35 patients was 84.07 ± 7.93 years, with the 80–89 age group accounting for the highest proportion (54.3%). The majority of patients were female, with a female-to-male ratio of 2:1. All patients presented with unstable fractures classified as AO type A2.2 (51.4%) or A2.3 (48.6%), and exhibited osteoporosis of grade II (60%) or grade III (40%) according to Singh’s index. Notably, 88.6% of patients had at least one comorbidity, with an average of 2.1 ± 1.0 comorbidities per patient. The most prevalent comorbidities were hypertension (62.9%), cardiovascular disease (34.3%), and diabetes mellitus (28.6%).Pain Relief: The mean Visual Analog Scale (VAS) pain score significantly decreased from 7.37±1.17 preoperatively to 3.6±1.06 postoperatively (p
Keywords: Intertrochanteric femoral fracture (IFF), cementless long-stem hemiarthroplasty, elderly patients.